(untitled) (MAUSAM, 1962)
The Yamuna which has been described in the Vedas (Bnrrard 1931) as one of the seven branches of the Gangs (Sapta-Sindhavas), drains the Punjab-11 umaon Himalayas from Simla in the northwest to Mussoorie in the southeast. In its Himalayan reach, its catch-ment lies between the two great Himalayan rivers, the Sutlej and the Ganga.